Comparison and combination of rotational imaging optical coherence tomography and selective plane illumination microscopy for embryonic study - Wu, Chen (Biomed Opt Express, 2017)
Several optical imaging techniques have been applied for high-resolution embryonic imaging using different contrast mechanisms, each with their own benefits and limitations. In this study, we imaged the same E9.5 mouse embryo with rotational imaging optical coherence tomography (RI-OCT) and selective plane illumination microscopy (SPIM). RI-OCT overcomes optical penetration limits of traditional OCT imaging that prohibit full-body imaging of mouse embryos at later stages by imaging the samples from multiple angles. SPIM enables high-resolution, 3D imaging with less phototoxicity and photobleaching than laser scanning confocal microscopy (LSCM) by illuminating the sample with a focused sheet of light. Side by side comparisons are supplemented with co-registered images. The results demonstrate that SPIM and RI-OCT are highly complementary and could provide more comprehensive tissue characterization for mouse embryonic research.